Community-based Ecotourism in Protected Areas towards Inclusive Development-An Evidence of Bhitarkanika Wildlife Sanctuary of India - Patita Paban Mohanty; Soumendra Kumar Patra; Velan Kunjuraman; Dhiraj Pathak (International Journal of Business and Society, 2024)
Community-based ecotourism (CBET) is one of the tourism segments used to protect the natural environment by the host communities in many countries; however, empirical studies involving active involvement, understanding, and level of satisfaction of the community and tourists in various ecotourism projects are still scarce in the context of developing countries. Thus, this study empirically examines the potential of community-based ecotourism in and around the Bhitarkanika Wildlife Sanctuary (BKWS) from the perspectives of the community and tourists in Odisha, India. Primary data were collected through a structured questionnaire prepared based on an expert view. In this study, both descriptive and exploratory research designs were considered the most appropriate. A total of 470 respondents participated in this study. Cronbach’s α was used to ensure reliability and validity of the instrument used for the survey. Data analysis was performed using SPSS 23.0. Collected data were tested for outliers using stem and leaf chart analysis, and all data were normally distributed for further analysis. Finally, a clear picture of the study was drawn based on the analysis and interpretation. The ANOVA (F-test) results demonstrated that community-based ecotourism was quite significant for inclusive development and conservation practices, as supported by all five statistically significant explanatory factors. The one-way ANOVA test for Hypothesis 1 found that community-based eco-tourism can be leveraged as a unique selling point (USP) to boost tourism in Odisha. Furthermore, one-way ANOVA was used to test the second hypothesis, which demonstrated that community-based ecotourism raises awareness within the local population about the importance of protecting Odisha's tourism resources. Similarly, the t-test results demonstrated that tourists and communities do not differ significantly in terms of satisfaction with event settings, art and craft, performance, infrastructure, guide services, and information. The findings of the study revealed that CBET was a major tool for promoting Odisha Tourism and creating awareness among the local community for the conservation of protected areas to embrace sustainability. Practical implications have been suggested for policy improvement in Odisha Tourism.